Blue-Light Filtering Intraocular Implants and Darker Irises Reduce the Behavioral Effects of Higher-Order Ocular Aberrations. (4th May 2022) - Renzi-Hammond, Lisa M.; Hammond, Billy R.
Abstract: Purpose: Higher order ocular aberrations (e.g. entopic scatter) arising from cornea and lens, decreases retinal image contrast by dispersing part of the image-forming optics over a broad retinal surface. Selective filtering of the light that is most susceptible to aberration (high-energy "blue" light) may reduce some of the behavioral effects. This was tested by comparing the performance of a blue-light filtering (BLF) vs a clear intraocular lens implant (IOL). Methods: 52 participants with IOL (BLF: AlconSN60AT; clear: AlconSA60AT; N = 98 test eyes; M = 67.33 ± 7.48 years; 58.8% Female; 25.5% non-White) were recruited. Our outcome measure was based on the minimum resolvable distance between two points of light (two-point thresholds), formed using broadband xenon or isolated short-wave energy (425 nm). Iris color was measured by visual inspection and comparison against standard images. Results: In the broadband condition, patients with BLF IOL had smaller two-point thresholds ( M = 17.17 ± 5.71 mm; F [1, 48] = 2.60; p = 0.045) than clear controls ( M = 20.93 ± 10.22 mm). Similar improvements were found in the short-wave condition ( M BLF = 17.02 ± 5.30; M clear =21.42 ± 10.99; p = 0.04). In the contralateral broadband comparison, eyes with the BLF had significantly smaller two-point thresholds ( M = 18.10 ± 10.47 mm; t = −2.90, p < 0.001) than the clear IOL ( M = 20.89 ± 10.61 mm). Similar effects were seen in the short-wave condition ( M BLF = 18.23 ± 9.88; M clear = 21.06 ± 10.47; p = 0.001). Darker iris color was related to reduced scatter across IOL types, in both shortwave ( F [2, 48] = 4.62, p = 0.02) and broadband ( F [2, 48] = 5.27, p = 0.009) conditions. Conclusions: Anterior screening, be it by a darker iris or a BLF IOL, is directly related to decreases in two-point light thresholds.